ڕەفتاری شەڕەنگێزی لە ڕوانگەی تیۆری فێربونی کۆمەڵایەتی (باندۆرا) - نصراللة, واحدة حمةويس; منصور, خوێندکاری ماستەر: محمد محمود (Sulaimani Journal for Humanities, 2023)
This study is considered one of the theoretical studies that relied on the use of social learning theory, which is considered one of the most important theories that have a significant contribution to the interpretation of psychological and social phenomena. This theory uses behavioral and human concepts to clarify psychological tasks based on the continuous interaction between the person and the surrounding environment on the grounds that the environment affects behavior. Besides, this theory is called the new behaviorist school, which sees aggression as a learned behavior. Hence, the study problem came as follows: Does the social environment effect on aggressive behavior? Thus, this study aims to know the effect of the environment surrounding of the individual on the commission of aggressive behavior. To achieve this goal, the descriptive approach was used. Accordingly, the study reached the following most important conclusions: There is a relationship between environmental influences and individual behavior, meaning that society has a significant influence on aggressive behavior. Individuals' imitation of aggressive models around them plays an important role in aggressive behavior
Keywords: Keywords Behavior; Aggressive Behavior